2022
DOI: 10.1021/acs.energyfuels.2c02912
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Microbial Community and Removal of Hydrogen Sulfide (H2S) Using a Bio-Inhibitor and Its Application under the Oil Reservoir Condition

Abstract: Hydrogen sulfide (H 2 S) is a toxic gas widespread in injected water of secondary oil recovery, having disadvantages of serious corrosion equipment, health risks, and higher operational costs. This study focused on the field application with nitrate and nitrite injection, which has been less examined in previous studies. A bioinhibitor (400 mg/L nitrate + 300 mg/L nitrite) was reinserted into the water of the M71 oilfield (Jianghan Basin, China) with serious souring. The concentration of H 2 S decreased by 83%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…croflora. A low rate of oxygen diffusion across the polycarbonate housing the reactors was hypothesized as a reason for the limited sulfate reduction activity and the possible promotion of sulfide oxidation [39][40][41][42] consistent with the detection of a high relative abundance of sulfide-oxidizing bacteria in two of the reactors [18]. The relatively low levels of sulfate reduction and dissolved iron suggested that the rate of corrosion was relatively slow.…”
Section: Introductionmentioning
confidence: 61%
“…croflora. A low rate of oxygen diffusion across the polycarbonate housing the reactors was hypothesized as a reason for the limited sulfate reduction activity and the possible promotion of sulfide oxidation [39][40][41][42] consistent with the detection of a high relative abundance of sulfide-oxidizing bacteria in two of the reactors [18]. The relatively low levels of sulfate reduction and dissolved iron suggested that the rate of corrosion was relatively slow.…”
Section: Introductionmentioning
confidence: 61%
“…Sulfide-oxidizing bacteria could oxidize sulfide formed by the sulfate-reducing bacteria, recycling the sulfur to more oxidized sulfur species [44]. Indeed, Deng et al [46], after injecting nitrate and nitrite into an oil field with high H 2 S concentrations, noted that as H 2 S concentration and SRB levels dropped, the relative abundance of both nitrate/nitrite reducers and sulfide-oxidizing bacteria rose. In our study, reactors 2 and 6 among the fuel-containing reactors were noteworthy for a high relative abundance of sulfide-oxidizing Arcobacter (Epsilonproteobacteria) and other taxa belonging to Alpha-and Gammaproteobacteria and Flavobacteriia with the potential for sulfide oxidation (Figures 5 and 6).…”
Section: How Might Oxygen Affect Sulfate Reduction?mentioning
confidence: 99%